The teaching by competences week: the school as a laboratory forge - Mariarosaria De Simone; Anna Muto (Firenze University Press, 2018)
This paper aims to describe a pilot experience about teaching by competences that was carried out in a school. Particularly, the purpose of this experience with primary school pupils is to highlight the importance of the experiential teaching promoting global development of children. As a matter of fact, working in real and challenging situations shall facilitate meaningful learning with a strong social feature by linking responsibly every action to the real community as well as by teaching everyone to play his/her own part democratically and complying, inclusively, with their own 'idiosyncratic generativity.   La settimana della didattica per competenze: il plesso come fucina laboratoriale Nel presente lavoro viene descritta l'esperienza pilota di didattica per competenze realizzata in un plesso scolastico. In particolare, attraverso la narrazione di tale percorso, nello specifico degli alunni della primaria, si è voluta sottolineare l'importanza di una didattica esperienziale grazie alla quale promuovere lo sviluppo globale dei bambini e delle bambine. Infatti lavorare in situazioni reali e sfidanti facilita apprendimenti significativi a forte connotazione sociale, legando, responsabilmente, ogni singola azione alla comunità reale nella quale si è inseriti, in questo caso scolastica, insegnando a ciascuno, democraticamente, a fare la propria parte, nel rispetto inclusivo della propria idiosincrasica generatività.